2017
DOI: 10.1142/s1758825117501101
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Flatwise Compression Property of Glass Fiber-Reinforced Polypropylene Corrugated Sandwich Panel

Abstract: Composite sandwich structures with cellular cores have wide application in many fields such as aerospace due to their excellent properties. Thermoplastic composite structure has superior impact resistance and recycling ability compared with conventional thermosetting. The glass fiber-reinforced polypropylene corrugated sandwich panels were fabricated by hot-pressing and hot-melting methods, and the flatwise compression property was experimentally investigated. Numerical simulations by use of ABAQUS VUMAT were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The out-of-plane compressive strength as function of density is plotted for traditional metal foams [34], aluminum egg-boxes [35] and recently developed thermoplastic sandwich structures [2426,35] in Figure 10. In a fairly large density range (<450 kg/m 3 ), the compressive strength of the CCF/PEEK lattice sandwich structure studied in this paper outperforms some metal materials [34,35], GF/PP corrugated cores [26] and CF/PP lattice cores [25]. Besides, the CCF/PEEK lattice structure exhibits the strength comparable to the SrPET lattice cores [24] but worse than the SrPET corrugated cores [36] at densities above 150 kg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The out-of-plane compressive strength as function of density is plotted for traditional metal foams [34], aluminum egg-boxes [35] and recently developed thermoplastic sandwich structures [2426,35] in Figure 10. In a fairly large density range (<450 kg/m 3 ), the compressive strength of the CCF/PEEK lattice sandwich structure studied in this paper outperforms some metal materials [34,35], GF/PP corrugated cores [26] and CF/PP lattice cores [25]. Besides, the CCF/PEEK lattice structure exhibits the strength comparable to the SrPET lattice cores [24] but worse than the SrPET corrugated cores [36] at densities above 150 kg/m 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Du et al. [26] fabricated the corrugated sandwich panels utilizing glass fiber reinforced polypropylene(GF/PP) composite, and the compression performance were studied experimentally. Liu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Jusoh et al [12] reviewed the natural fiber composites as potentially used for corrugated core structures. Du et al [13] stated that skins made of biofiber based paper-reinforced polymer showed comparable flexural properties to the glass fiber reinforced polyurethane skins. An investigation on the mold design and manufacturing considerations of honeycomb made of kenaf/epoxy composite has been carried out by Manan et al [14].…”
Section: Właściwości Mechaniczne Pod Obciążeniem Quasi-statycznym Rdzmentioning
confidence: 99%
“…There has been some works in field of TPC, but it is still in the initial stage [20][21][22][23][24]. Chen et al [25][26][27] fabricated thermoplastic corrugated sandwich structures and conducted a series of studies on their quasi-static compression performance. At present, majority of studies mainly focus on the quasi-static mechanical properties of TPC sandwich structures, while the research on their dynamic properties is relatively lacking.…”
Section: Introductionmentioning
confidence: 99%